The First Annotated Genome Assembly of Macrophomina tecta Associated with Charcoal Rot of Sorghum. (1st June 2022) - Poudel, Barsha; Purushotham, Neeraj; Jones, Ashley; Nasim, Jamila; Adorada, Dante L.; Sparks, Adam H.; Schwessinger, Benjamin; Vaghefi, Niloofar
Abstract: Charcoal rot is an important soilborne disease caused by a range of Macrophomina species, which affects a broad range of commercially important crops worldwide. Even though Macrophomina species are fungal pathogens of substantial economic importance, their mechanism of pathogenicity and host spectrum are poorly understood. There is an urgent need to better understand the biology, epidemiology, and evolution of Macrophomina species, which, in turn, will aid in improving charcoal rot management strategies. Here, we present the first high-quality genome assembly and annotation of Macrophomina tecta strain BRIP 70781 associated with charcoal rot symptoms on sorghum. Hybrid assembly integrating long reads generated by Oxford Nanopore Technology and short Illumina paired-end reads resulted in 43 contigs with a total assembly size of ∼54 Mb, and an N50 of 3.4 Mb. In total, 12, 926 protein-coding genes and 7, 036 repeats were predicted. Genome comparisons detected accumulation of DNA transposons in Macrophomina species associated with sorghum. The first reference genome of M. tecta generated in this study will contribute to more comparative and population genomics studies of Macrophomina species.